AKTUALISASI DIRI PADA PENCAPAIAN TUJUAN PENDIDIKAN ISLAM DALAM PENGEMBANGAN KETERAMPIAN SOFT SKILL - Ahmad Zain Sarnoto; Laela Fitriyani (Jurnal Statement : Media Informasi Sosial dan Pendidikan, 2020)
Succesfull and achievement of a person in various aspects of life is not determined solely by academic knowledge and technical skill (hard skill). But more to the ability to manage yourself and others ( soft skill). This is in line with what was stated by Patton, who stated "psychologists agree that IQ only accounts for about 20% of the factors that determine success, the remaining 80% come from other factors, including what is meant by emotional intelligence". The results of this study mention that the process of developing soft skills in service participants at STAI Nurul Iman is neat and organized with a unique system, the outputs produced are able to actualize themselves, because the educational process lasts long, systematic and continuous. The researcher used a descriptive qualitative research approach. While the data collection method uses interview, observation, and documentation techniques. then the validity of the data uses the triangulation technique